Spontaneous cutaneous soft tissue sarcoma with differentiation into fibroblasts in a Sprague-Dawley rat - Ogawa, Takashi (J Toxicol Pathol, 2016)
A small mass with an ulcer was found in the skin of the dorsal cervix of a 7-month-old male Sprague-Dawley rat. Histologically, the central region of the tumor showed a high cellular density with oval-shaped tumor cells arranged in an alveolar pattern and thin collagen fiber bundles. The peripheral region of the tumor had a low cellular density with short spindle- or polygonal-shaped tumor cells surrounded by abundant collagen fiber bundles. Immunohistochemically, the tumor cells were strongly positive for vimentin and proliferating cell nuclear antigen, and a portion of the short spindle- or polygonal-shaped cells located in the peripheral region of the tumor were positive for S100A4. However, the tumor cells were negative for alpha-smooth muscle actin, desmin, S100, chromogranin A, neurofilament, CD68, Iba-1, cytokeratin 20, von Willebrand factor, melanosome, and anti-melanoma. Electron microscopically, the tumor cells had an abundance of rough endoplasmic reticulum, the Golgi apparatus, and a few intracellular collagen fibrils, showing fibroblastic features. Considering the lack of diagnostic differentiation, the tumor was diagnosed as an undifferentiated malignant mesenchymal tumor and classified as a soft tissue sarcoma with differentiation into fibroblasts in a portion of the tumor cells.